Viromes of ten alfalfa plants in Australia reveal diverse known viruses and a novel RNA virus - Samarfard, Samira (2020)
Alfalfa plants in the field can display a range of virus-like symptoms, especially when grown over many years for seed production. Most known alfalfa viruses have RNA genomes, some of which can be detected using diagnostic assays, but many viruses of alfalfa are not well characterized. This study aims to identify the RNA and DNA virus complexes associated with alfalfa plants in Australia. To maximize the detection of RNA viruses, we purified double-stranded RNA (dsRNA) for high throughput sequencing and characterized the viromes of ten alfalfa samples that showed diverse virus-like symptoms. Using Illumina sequencing of tagged cDNA libraries from immune-captured dsRNA, we identified sequences of the single-stranded RNA viruses, alfalfa mosaic virus (AMV), bean leafroll virus, a new emaravirus tentatively named alfalfa ringspot-associated virus, and persistent dsRNA viruses belonging to the families Amalgaviridae and Partitiviridae. Furthermore, rolling circle amplification and restriction enzyme digestion revealed the complete genome of chickpea chlorosis Australia virus, a mastrevirus (family Geminiviridae) previously reported only from chickpea and French bean that was 97% identical to the chickpea isolate. The sequence data also enabled the assembly of the first complete genome (RNAs 1–3) of an Australian AMV isolate from alfalfa.